Surface Metal/Nonmetal Mine Fires - Maria I. De Rosa (The National Institute for Occupational Safety and Health (NIOSH), 2004)
Table 19 and figure 7 show the number of fires and fire injuries for surface metal/nonmetal mines by state during 1990-2001. Table 19 also shows the injury risk rates, employees' working hours, and lost workdays. A total of 79 fires occurred in 16 states during 1990-2001 for these mines. Forty-five of the fires caused 44 injuries and 2 fatalities (including 9 fires and 7 injuries involving contractors). The yearly average was 6.6 fires and 3.7 injuries. Sixty-five fires with 31 injuries and 2 fatalities occurred at metal mines, and 14 fires with 13 injuries occurred at nonmetal mines. The Ewhr value was 546 x 106 hr (In = 0.016), and the LWD value was 13,134. Nevada and Arizona had the most fires (19 fires, 10 injuries, and 1 fatality; and 19 fires and 11 injuries, respectively). They were followed by Minnesota (11 fires, 4 injuries, and 1 fatality) and Alaska (6 fires and 4 injuries). Of these states, Alaska had the highest injury risk rate value (In = 0.079). Table 20, partly illustrated in figure 8, shows the number of fires, fire injuries, fire fatalities, risk rates, employees' working hours, and lost workdays by time period. The number of fires increased during the second period, then decreased during most of the remaining periods. The number of fire injuries decreased during most of the periods (a small increase is seen during the last period), accompanied by a decline in employees' working hours during most of the periods (a small increase is seen during the third and fourth periods). The In values follow patterns similar to those shown by the number of fire injuries. Tables 21-26 show the number of fires by ignition source, method of detection and suppression, equipment involved, location, and burning material by time period. Figure 9 shows the major variables related to fires for 1990-2001. Table 27 shows the number of fire injuries per number of fires causing injuries and total fires by year, ignition source, equipment involved, and location.